Rancang Bangun Alat Pelurus Puncher Bar - Wahab, Abd.; Hamarung, Mukhlis A. (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
Round bar material with a diameter of 25,4mm is a type of material commonly used in the field of building construction and machinery spare parts. At PT. Vale Indonesia Tbk., this material is fabricated according to its design, which is called a puncher bar. A puncher bar is a tool used to clean the tuyere hole from nickel matte blockages in the PT converter section. Vale Indonesia. A series of cleaning processes can cause the puncher bar to bend at the ends or in the middle. The bent puncher bar was straightened manually in the production workshop of the Soroako Technical Academy. The process of straightening the puncher bar manually is considered less effective in terms of safety, time efficiency and worker productivity. The design of this machine consists of several components, namely the machine frame, electric motor, speed reducer, gears, towing roller, and towing roller. The stages of making a machine start from design, manufacturing, assembly, and testing. The puncher bar straightening machine has dimensions of 930 mm x 702 mm x 1129 mm with a main drive of a 5.5 HP electric motor with 1440 rpm. Vee belts and gears as rotation transmitters. The towing roller uses AISI 4140 alloy steel with a diameter of 5 inches and the guide roller uses mild steel with a diameter of 4 inches. This machine can straighten puncher bars with a maximum bend of 6 cm with a final bend of 1.5 cm with a processing time of 1 minute